Exploring Students’ Perceptions of the English for General Communication Class and Its Impact on Speaking Skills - Diah Rini Melati; Dameria Magdalena Sidabalok (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The study investigates student perceptions of English for General Communication classes in enhancing their English-speaking skills at the English Language Laboratory, Bandar Lampung University, during the odd semester of 2023/2024. This quantitative descriptive research employed a survey method, utilizing questionnaires for data collection and descriptive statistical analysis through percentages. The study population consisted of 382 students enrolled in the English for General Communication classes, with a randomly selected sample of 284 students (10% of the total). The findings reveal that student perceptions of the course were largely positive, with 2.5% (7 students) rating it as very positive, 49.3% (140 students) as positive, 24.3% (69 students) as moderate, 10.9% (31 students) as negative, and 13.0% (37 students) as very negative. Overall, the results indicate that the majority of students perceive the English for General Communication classes as beneficial for developing their speaking skills, categorizing their perceptions within the positive range. These findings suggest that the course plays a significant role in enhancing students' English-speaking abilities, highlighting the effectiveness of the teaching methods and learning environment provided at the English Language Laboratory. The study underscores the importance of continuously improving instructional strategies and resources to further support students in their language acquisition journey.